Elevated capillary blood glucose values prior to [18F]FDG-PET are common in patients with gastrointestinal tumors: a real-world clinical analysis - Antonio Giulio Gennari; Joan Walter; Bojan Bojanic; Nadia Fehr; Alexia Rossi; Thomas Sartoretti; Moritz Schwyzer; Philipp Saurer; Katharina Binz; Matthias Ernst; Martin Huellner; Michael Messerli (Journal of Cancer Research and Clinical Oncology, 2026)
Abstract Purpose Gastrointestinal (GI) tumors and diabetes are interconnected; however, the latter is often undiagnosed. This study aimed to provide real-world data on glycemic profiles in patients with GI tumors by measuring capillary fasting blood glucose (cFBG) prior to fluorodeoxyglucose positron emission tomography ([ 18 F]FDG-PET) scans. Methods 159 consecutive patients with GI tumors who underwent a clinically indicated [ 18 F]FDG-PET from June 2023 to February 2024 were included. In patients fasting >4 h, cFBG was measured before [ 18 F]FDG administration and PET image acquisition and classified according to American Diabetes Association guidelines into: <100 mg/dL (< 5.6 mmol/L), 100–125 mg/dL (5.6–6.9 mmol/L), and ≥ 126 mg/dL (≥ 7.0 mmol/L). Diabetes awareness and common diabetes risk factors were assessed via a questionnaire, and visceral fat was measured from anatomical images. A sensitivity analysis compared cFBG levels between patients scanned before and after 11 a.m. Results 86 (58%) and 21 (13%) patients showed cFBG values of 100–125 mg/dL (5.6–6.9 mmol/L) or ≥ 126 mg/dL (≥ 7.0 mmol/L), respectively. Of the 145 (97%) patients who responded to our questionnaire, 24 (17%) reported being diabetic. Greater diabetes awareness correlated with higher cFBG values ( p < 0.001). Only 13 (54%) of patients who reported being diabetic had cFBG of 125 mg/dL or lower (< 7 mmol/L), indicating insufficient glycemic control in many patients. cFBG values were higher in cases evaluated before 11 a.m. than afterward ( p < 0.001). Conclusion Impaired glycemic control was prevalent among patients with GI tumors. Further, a relevant fraction of those who reported being diabetic had a suboptimal glycemic metabolism and control. This underscores the importance of enhancing glycemic control screening practices.